Impact of ischaemic preconditioning on experimental steatotic livers following hepatic ischaemia–reperfusion injury: a systematic review. Issue 1 (January 2015) - Chu, Michael J.J.; Vather, Ryash; Hickey, Anthony J.R.; Phillips, Anthony R.J.; Bartlett, Adam S.J.R.
Abstract: Background: Steatotic livers are vulnerable to the deleterious effects of ischaemia–reperfusion injury (IRI) that occur after hepatic surgery. Ischaemic preconditioning (IPC) has been shown to abrogate the effects of IRI in patients undergoing hepatic surgery. Experimental studies have suggested that IPC may be beneficial in steatotic livers subjected to IRI. Objective: The aim of this systematic review was to evaluate the effects of IPC on steatotic livers following hepatic IRI in experimental models. Methods: An electronic search of the OVID Medline and EMBASE databases was performed to identify studies that reported clinically relevant outcomes in animal models of hepatic steatosis subjected to IPC and IRI. Results: A total of 1093 articles were identified, of which 18 met the inclusion criteria. There was considerable heterogeneity in the type of animal model, and duration and type of IRI. Increased macrovesicular steatosis (> 30%) was associated with a poor outcome following IRI. Ischaemic preconditioning was found to be beneficial in > 30% steatotic livers and provided for decreased histological damage, improved liver function findings and increased survival. Conclusions: Experimental evidence supports the use of IPC in steatotic livers undergoing IRI. These findings may be applicable to patients undergoing liver surgery. However, clinical studies are required to validate the efficacy of IPC in this setting.